READING SKILLS IN INDIVIDUALS WITH MACULAR DEGENERATION (Annual of the Faculty of Philosophy in Skopje, 2019)
Macular degeneration (MD) involves a whole range of progressive and degenerativechanges in the macula. Though central vision is affected, peripheral visionusually remains preserved in MD. Unfortunately, there is a lack of effective medicaltreatment for most MD, therefore it is important to focus efforts on the developmentof visual compensatory mechanisms.People with macular degeneration experience difficulties in reading due tocentral-field loss. Reading skills is the primary difficulty and at the same time theprimary goal for individuals with macular degeneration seeking vision rehabilitation.The current prevalent methods for reading skills training are magnification—large print size and scotoma awareness training. Also, more recent studies showedthat specific oculomotor training, avoiding visual crowding and special fonts are allbeneficial to reading skills rehabilitation. The focus of this article is to review anddiscuss the methods and adaptations available today that we can use in rehabilitationof reading skills in individuals with MD.
Keywords: MACULAR DEGENERATION; READING; ECCENTRIC VIEWING; FONTS